UPAYA PEMULIHAN EKONOMI INDONESIA PASCA COVID-19 MELALUI FORUM DIGITAL ECONOMY WORKING GROUP (DEWG) G20 - Arif, Ali Hanafi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The COVID-19 pandemic has significantly impacted global economies, including Indonesia, causing economic disruptions across various sectors, particularly Micro, Small, and Medium Enterprises (MSMEs). As a response, Indonesia leveraged its presidency at the G20 in 2022 to promote digitalization through the Digital Economy Working Group (DEWG). This research explores Indonesia's efforts in utilizing the DEWG as a platform for economic recovery by focusing on three key priorities: Connectivity and Post-COVID-19 Recovery, Digital Literacy and Skills, and Cross-Border Data Flow and Data Free Flow with Trust. Using a qualitative-descriptive method, this study analyzes Indonesia's strategy in proposing digitalization as a critical recovery pathway and how these efforts align with its national interests and G20 commitments. The research also evaluates the outcomes of the DEWG, particularly the Bali Package, a consensus document encompassing recommendations and strategies for inclusive and sustainable digital transformation. Findings reveal that Indonesia's presidency successfully spotlighted the strategic importance of digital connectivity in addressing economic challenges post-pandemic. Initiatives such as expanding digital infrastructure, promoting digital literacy programs, and advocating for secure cross-border data flow demonstrated Indonesia's proactive diplomacy and leadership within the G20. Furthermore, the DEWG provided a platform for Indonesia to champion the interests of developing countries while facilitating collaborative solutions for global digital transformation. Keywords: G20, Digital Economy Working Group, digital transformation, Indonesia, digital diplomacy, MSMEs, global economy